Carbohydrate and Lipid Dynamics in Wheat Crown Tissue in Response to Mild Freeze–Thaw Treatments. Issue 4 (1st July 2014) - Skinner, D. Z.; Bellinger, B. S.; Hansen, J. C.; Kennedy, A. C.
ABSTRACT: Freezing tolerance resulting from cold hardening is critical to survival of fall‐seeded winter wheat. Exposure of winter wheat plants to cycles of freeze–thaw at temperatures just below, and just above freezing results in incremental improvements of freezing tolerance. Changes in the concentrations of carbohydrates in the cellular fluids of wheat crowns, and of lipids extracted from wheat crown tissue, were quantified following exposure to 24 h freeze(s) at –3°C, with or without a following thaw of 24 h at 3°C. Concentrations of simple sugars, and sucrose and related carbohydrates, increased in the first 24 h of exposure to –3°C, and continued to increase whether the plants were then exposed to a further 24 h at –3°C or were exposed to 3°C for 24 h. The concentration of fructans decreased during the first 24 h of exposure to –3°C, and continued to decrease if the plants were exposed to 3°C for 24 h, but increased if the plants were exposed to a continuous –3°C for 48 h. The frequencies of occurrences of numerous lipid species changed with each 24 h temperature treatment, some consistent with the behavior of lipid signaling molecules. Carbohydrates and lipids in wheat crowns are actively restructured at subzero temperatures as the plants acquire greater freezing tolerance. Identifying plant lines especially able to effect this restructuring may enable the development of plant lines with improved freezing tolerance.